Faktor Risiko Lingkungandan Kebiasaan Penduduk Berhubungan Dengan Kejadian Filariasis di Distrik Windesi Kabupaten Kepulauan Yapen Provinsi Papua - Yulius Sarungu Paiting; Onny Setiani; Sulistiyani Sulistiyani (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background : Regency of Kepulauan Yapen through Finger Blood Survey in 2006 was established as a filariasis endemic region. In 2007 started the implementation of mass treatment was held once a year for 5 years. Based on the survey of microfilaria at January 2010, the microfilaria ratewas 2.06%, where the largest number of people was in the District Windesi. Method : The study was an analytic survey with a case control approach. Population was resident in the village of Saruman and Windesi. The determination of the cases and control was done trough screening tests and found 10 cases of Wuchereria bancrofti.The ratio 1: 2, then the number of samples was 30, which was matched by age, sex and type of work. Result : The results were characteristics of filariasis patients, 30% in ≤ 20 year age group (≥ 15 years) and 21-30 years, 50% as farmers, 70% low income level (<Rp. 500,000) and 60% low level education (elementary school). Physical environmental conditions (average temperature of 26.75 0C, humidity of 83.61%, and 275.5 mm of rainfall and wind speed 4.07 knots). Chemical environmental conditions had the average pH of 6.69 and 1.14% salinity.There was significant correlation between presences of a pool of water with the incidence of filariasis.There was not significant correlation between presencesof aquatic plants, habits of using musquito net, hanging clothes, outside the house at night, and conduct environmental management with the incidence of filariasis. The dominant risk factor are existence of forest/bush (p value: 0.027, OR: 9.727; 95% CI: 1.290 to 73.333) and completeness of clothing when tappingof sago (p value: 0.045, OR: 7.327; 95 % CI: 1.048 to 51.213). Someone who lived in a house close to bushes/forest and has a habit of not using fully clothed when tapping of sago, the probability of suffering from filariasis of 79.43%. Keywords : filariasis, environmental risks, habit, Saruman, Windesi